Nurturing Learner Autonomy to Enhance Motivation and Academic Achievement for the L2 Learners in ESL Contexts (IUBAT Review, 2024)
This This review explores the pivotal role of nurturing learner autonomy in enhancing motivation and academic achievement in English as a Second Language (ESL) contexts. It examines the multifaceted construct of learner autonomy, including self-regulation, metacognitive strategies, and self-directed learning. The review investigates how promoting learner autonomy can positively influence intrinsic motivation, self-efficacy, and persistence, which are essential for successful language learning. It scrutinizes instructional practices, learning environments, and pedagogical interventions that foster learner autonomy, such as learner-centered approaches, providing choices, and encouraging self-assessment and goal-setting. Furthermore, the review critically evaluates the impact of learner autonomy on academic achievement across diverse educational levels and cultural backgrounds, while exploring potential challenges and limitations. Ultimately, it offers practical implications for educators, curriculum designers, and policymakers, emphasizing the importance of empowering learners and cultivating an autonomous learning mindset to enhance motivation and academic achievement in ESL contexts.IUBAT Review—A Multidisciplinary Academic Journal, 7(2): 176-196